Real-time RT-PCR for quantitative detection of Plum pox virus - Olmos, Antonio; Bertolini, Edson; Gil, Maite; Cambra, Mariano (2017)
Two protocols for real-time quantitative detection of Plum pox virus (PPV) and identification of PPV-D and PPV-M isolates were developed using the intercalating dye SYBR-Green I and TaqMan chemistry. SYBR-Green I method using the universal PPV primers, P1 and P2, required for its optimization an accurate analysis of primers concentration to avoid primer-dimer formation. Optimization for TaqMan technology required the design of new primers and internal probes using the Primer Express software and the alignment of available PPV sequences from Genbank, EMBL, and DDBJ databases. Although the two methods were able to detect as low as 4 copies of transcripts, only the TaqMan method maintained this sensitivity when plant material was used. In addition, the use of TaqMan technology succeed in the detection and quantification of PPV targets in single aphids.